School Readiness Profiles and Growth in Academic Achievement - Pan, Qianqian; Trang, Kim T.; Love, Hailey R.; Templin, Jonathan (Frontiers in Education, 2019)
The purpose of this research was to identify the presence of different school readiness profiles and to determine whether profiles could differentially predict academic growth. The Early Childhood Longitudinal Study: 2010-11 (ECLS-K: 2011) public data set was used, and participants were 14,954 first-time kindergarteners. The age of entering kindergarten ranged from 44.81–87.98 months with a mean of 76.13 months. In Study 1, a six-dimensional construct of school readiness was used: health, self-regulation, social and emotional development, language development, cognitive development, and approaches to learning. Results revealed 41 profiles with the top six school readiness profiles covering 85% of the sample: (1) Positive Development (28%); (2) Comprehensive At-Risk (24%); (3) Personal and Social Strengths (20%); (4) Cognitive and Language Strengths (5%), (5) Health Strength (5%); and (6) Cognitive, Personal and Social Strengths (3%). Study 2 examined whether school readiness profiles could predict children’s reading and math achievement growth using growth curve models. Results showed that different school readiness profile membership had unique academic growth patterns and could predict academic growth above and beyond child and family background variables. Moreover, children with the Positive Development profile had higher academic achievement over time. Children with the Personal and Social Strengths profile had the largest growth rates. In sum, findings support the inclusion of self-regulation as another dimension of school readiness and the important role of personal and social skills in the development of reading and math achievement.